An ecofeminist study of Barbara Kingsolver’s Animal Dreams and Prodigal Summer - Ali, Ridha’a; Sasani, Samira (Research Journal in Advanced Humanities, 2024)
Ecofeminism has pervaded many disciplines such as science, philosophy, politics, and literature. It emphasizes the ultimate interconnectedness of lifecycle. Ecofeminists contend that any shot to liberate and release women won’t be fruitful and prolific without the liberation of nature. This article intends to study the woman/nature interconnectedness with ecofeminist perception in Kingsolver’s selected two novels Animal Dreams and Prodigal Summer. It, strictly, challenges environment, animal elimination and how the female protagonists using their environmental consciousness, creating some connections with natural settings and imitates a union between women and nature. The study, indeed, focuses on women (feminism) and nature (ecology) under the authority of men. Ecofeminists attempt to find solutions for the social problems and the diseased cultural masculine system of the societies. Thus, they attempt to examine women and nature and the way they react against the masculine, misogynists, and unequal communities. Hence, they insist to mirror themselves as the source of life. Life will be continued by women who are the backbones of civilizations and families. They deliver courage, nurturing, provision, maintenance and are vital to the development of the children. Consequently, they have the right to take on leadership roles in communal organizations.